ANALYSIS OF EMPLOYEE WAGE SYSTEM: Case Study on Brokerage UMKM in Sukosewu Village, Blitar - Diana Elvianita Martanti; Eva Sofiatul Imanah (Universitas Islam Balitar, 2019)
This study aims to find out how the employee wage system in MSMEs in Blitar Regency is UMKM Rumah Bros. This research was carried out in one of the MSMEs in Blitar, namely Bros House located in Sukosewu Village, RT. 03 RW. 01 Gandusari District. UMKM Rumah Bros is engaged in brooch making. Wage systems and procedures for MSMEs have an important role in achieving business success. If the wage system and procedures are well implemented, the wage process will be organized so that it does not create disparity and jealousy among employees. Data collection techniques in this study were observation, interviews, and documentation. Observation is carried out by conducting direct reviews and observations on the implementation of employee remuneration. Interviews are conducted by asking a number of questions with the business owner and other employees concerned with the research conducted. Documentation is done by collecting relevant data. After collecting the data needed in the study, the researcher conducted an analysis. The analysis was carried out by triangulation. The researcher used data triangulation, method triangulation, and theory triangulation. The results showed that the employee salary system at UMKM Rumah Bros had been carried out quite well. This can be seen from the network and procedures that include the functions of the related parts, the documents used, the accounting records used, and the wage system applied.